Ameliorating effects of DPP (Phoenix dactylifera L.) extract on serum gonadotropins and Prolactin hormones in mature female rats exposed to sodium nitrite - M. J. Jiheel; J. K. Arrak (Kufa Journal for Veterinary Medical Sciences, 2018)
This study was accomplished to explore the role of crude ethanol extract of date palm pollen grains (DPP) in ameliorating the induction of oxidative stress by sodium nitrite in female rats.